Racial and ethnic differences in cost-of-care conversations among older adults. (3rd July 2022) - Conner, Kyaien O.; Wiltshire, Jacqueline; Garcia, Edlin Colato; Langland-Orban, Barbara; Anderson, Erica; Carrion, Iraida; Goodman, Amber; Goodman, Ashley
ABSTRACT: Background: The rapidly growing racially diverse ageing population in the United States presents unique challenges for the country's social, economic, and healthcare systems. Rising health care costs, increased patient cost-sharing, and limited financial resources make this generation of older Americans susceptible to large medical bills or debt, which disproportionally impacts older adults who are from racial/ethnic minority communities. Cost of care (CoC) conversations between patients and healthcare providers is one recommended approach for containing healthcare costs and alleviating patients' financial burden of care. Method: The current study used focus group methods to qualitatively explore the contextual factors that influence CoC conversations in a diverse sample of older adults (N = 27). Three focus groups were held with non-Hispanic White (n = 10), Black/African American (n = 9), and Hispanic (n = 8) participants. Thematic analysis yielded four broad themes. Results: The results suggest that CoC conversations do not occur with physicians. The facilitators of CoC conversations included positive provider affect, rapport/relationship building, and communication. Barriers included lack of physician training, wait time, lack of focus on the patient, language, provider preferences, fear of physicians, and religion. There were significant differences in the facilitators and barriers across racial/ethnic groups. Conclusions: It is critical for physicians to have the tools and training to successfully discuss CoC with older patients. Cultural competency training and provider awareness of patient preferences and expectations may be important when it comes to enhancing rapport and increase the likelihood of these important conversations within racial/ethnic minority communities.